TANGGUNG JAWAB SOSIAL PERUSAHAAN KEMITRAAN DAN BINA LINGKUNGAN KABUPATEN SUKABUMI STUDI-KASUS PADA STAR ENERGY GEOTHERMAL - Ghaiba, Farah (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2025)
Corporate Social Responsibility is a corporate responsibility to the community, as stated in the Sukabumi Regency Regional Regulation Number 6 of 2014. The purpose of this study is to review the responsibility of Star Energy Geothermal Salak (SEGS) to the community and the environment. As well as how the Sukabumi district government handled the case that occurred at Star Energy Geothermal Salak. This research method uses normative juridical, and the description used is descriptive. The results of the study show that the synergy and clarity of a regulation must be considered. Star Energy Geothermal has carried out Corporate Social Responsibility. However, the existence of obstacles and interference from the outside makes the programs carried out do not according to the wishes of the community, resulting in new demands and agreements according to the wishes of the community.